Acute Synthetic Cannabinoid Toxicity Simulation - Paolo Grenga; Matthew Sarsfield; Elliot Rodriguez (Association of American Medical Colleges, 2015)
Abstract Introduction Synthetic cannabinoids refer to a formidably varied array of synthetic THC receptor agonists used to achieve euphoria typically by way of smoking or ingestion. In addition to their euphoric effects, however, synthetic cannabinoids are known to cause psychosis, agitation, elevated vital signs, myocardial ischemia, and seizures. Unfortunately, there is no specific toxidrome associated with this type of toxicity. Use of products containing these chemicals has been increasing in recent years, prompting clinicians to increase their index of suspicion for synthetic cannabinoid use in intoxicated patients. This rersource is a high-fidelity case simulation of a patient experiencing acute synthetic cannabinoid toxicity. Methods Primary target learners included medical students on emergency medicine acting internship/subinternship rotations and emergency medicine residents. Additional target learners could include internal medicine residents and residents and students on toxicology rotations. Roles, including a team leader, a member tasked with conducting the physical exam, and a recorder, were assigned prior to the simulation. Students were allowed to share roles if necessary. Structured debriefing followed completion of the simulation. After debriefing, a supplemental handout was distributed to the students. Results Two pilot-testing sessions of this simulation have been well received by emergency medicine acting interns and fourth-year medical students interested in specialties other than emergency medicine. Feedback from these sessions was universally positive and has been used to refine the execution of the case scenario. Discussion This case simulation highlights the pathophysiology, presentation, identification, and treatment of synthetic cannabinoid toxicity and is based in part on an actual patient presenting intoxicated in this manner. The controlled environment of the simulation laboratory allows learners in both medical school and residency the opportunity to act as the primary caregiver for patients presenting with this pathology.